Notes from Notes on Blindness: The challenges of the in-house1 film production model in independent cinema. Issue 2 (1st December 2018) - Petkovic, Dusan
This article, derived from a larger ethnographic research created around the production of the award-winning independent film Notes on Blindness (2016) and conducted by a researcher active as a film professional, explores the deeper consequences of choosing to pursue a production 'in-house'. Through participant observation, Actor-Network Theory and negotiation between film practice and research, the researcher finds independent filmmakers caught between the opposing trends of high-end industry and the digital economies. The organization forms observed in this article stand opposite to the prevalent globalized creative labour trends motivated by the internet and new technologies, and can best be described as a revival of Richard Sennett's craft workshop in the digital era. These are ultra-dense creative spaces where craftspersons nurture their creative impulses and shield them from the negative aspects of the technological and economic upheaval. In the hope that the findings will inform future filmmakers in the role of this specific type of organization in delivering the intended output, this article offers insights beyond the industry self-avowal and sales pitch.